Balance sheet analysis of joint stock companies listed at the Karachi Stock Exchange - State Bank of Pakistan (Karachi : State Bank of Pakistan, 2009)
This analysis is based on the published balance sheets of non-financial companies listed at the Karachi Stock Exchange. For the purpose of comparison, the analysis of the five previous years is included in each years publication.
HQ Library has 2002-2007
oif 30/09/2019
Ref.
Keywords: Stock companies; Karachi Stock Exchange; Accounting; Pakistan; Financial statements; Pakistan